Improving equity in health care financing in China during the progression towards Universal Health Coverage - Mingsheng Chen; Andrew J. Palmer; Lei Si (BMC, 2017)
Abstract Background China is reforming the way it finances health care as it moves towards Universal Health Coverage (UHC) after the failure of market-oriented mechanisms for health care. Improving financing equity is a major policy goal of health care system during the progression towards universal coverage. Methods We used progressivity analysis and dominance test to evaluate the financing channels of general taxation, pubic health insurance, and out-of-pocket (OOP) payments. In 2012 a survey of 8854 individuals in 3008 households recorded the socioeconomic and demographic status, and health care payments of those households. Results The overall Kakwani index (KI) of China's health care financing system is 0.0444. For general tax KI was −0.0241 (95% confidence interval (CI): −0.0315 to −0.0166). The indices for public health schemes (Urban Employee Basic Medical Insurance, Urban Resident's Basic Medical Insurance, New Rural Cooperative Medical Scheme) were respectively 0.1301 (95% CI: 0.1008 to 0.1594), −0.1737 (95% CI: -0.2166 to −0.1308), and −0.5598 (95% CI: -0.5830 to −0.5365); and for OOP payments KI was 0.0896 (95%CI: 0.0345 to 0.1447). OOP payments are still the dominant part of China's health care finance system. Conclusion China's health care financing system is not really equitable. Reducing the proportion of indirect taxes would considerably improve health care financing equity. The flat-rate contribution mechanism is not recommended for use in public health insurance schemes, and more attention should be given to optimizing benefit packages during China's progression towards UHC.